IMPLEMENTASI PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Siti Humulhaer; Rommy Pratama (SUPREMASI HUKUM, 2021)
Corruption is a crime that becomes an obstacle to the development of the life of the nation and state. Especially in an effort towards the national development process. Corruption can be declared as an extra ordinary crime because it has a massive impact on the economy, so this crime must be eradicated by a structured system of laws and regulations and followed by state apparatus, especially those related to government officials in the field of law in Indonesia, law enforcement agencies. those who handle crimes of corruption include the Indonesian National Police, the Attorney General's Office, the Corruption Eradication Commission (KPK), the Justice (Corruption Crime Court). The purpose of handling problems relating to legal issues of corruption is to protect the state financial budget from being misused in its use, in the sense that institutions, organizations, institutions, regional heads who are entrusted by the state with a planned budget must be used in accordance with the allocated funds. has been approved and stipulated by the government by being absorbed in predetermined programs and must also be recorded and reported and accounted for in accordance with existing regulations. The prevailing laws and regulations include the Criminal Code (KUHP), but it must be more in accordance with the times and developments in the life of a nation in the development process which can be used as a strong legal basis for the prevention and eradication of corruption problems, in this case there must be a special law regulating corruption other than the Criminal Code with the aim of This is a legal basis for harmonization to prevent and eradicate corruption in Indonesia. This study uses a library research method by collecting sources of information through data from various references which are then used as research writing. The conclusion of this study is that the government has paid special attention to the implementation of prevention, eradication and law enforcement of corruption by publishing the products of legal regulations in every era of government. Keywords: Corruption, Extraordinary Crime, Corruption Law